Diving deep into the network: Quantifying protection effects across California's marine protected area network using a remotely operated vehicle - Nicholas R. Perkins; Andrew Lauermann; Michael Prall; Geoffrey R. Hosack; Scott D. Foster (Conservation Science and Practice)
Abstract Networks of marine protected areas (MPAs) are being increasingly implemented worldwide as conservation management tools. We report here on MPA effectiveness using data from a 17‐year long remotely operated vehicle (ROV) monitoring program spanning mesophotic (~ 20–130 m) depths in 26 MPAs across California's MPA network. We utilize a spatial modeling approach that includes important environmental covariates as well as spatial dependence in the data, and allows the separation of statewide and regional trends in the abundance of focal species from additional trends specific to MPAs. We demonstrate that there have been statewide and/or regional recoveries in abundance for the majority of our 10 focal demersal fish species, with all four statewide species assessments and 18 out of 22 species‐region combinations assessed displaying positive trends. We also demonstrate that MPA protection has had an additional positive effect on the abundance of the majority of these focal species inside MPAs compared with reference areas, with positive effects for all four statewide species, and 18 out of 22 statewide/regions assessed showing positive effects, four showing no statistically detectable differences, and no negative MPA effects found. Comparisons with theoretical expectations of MPA recovery for our focal species showed that 2 out of 4 statewide, and 11 out of 17 species‐region combinations assessed displayed higher mean MPA effects than expected. Our results highlight strong trajectories of increasing abundance and additional MPA effects for many of our focal species, demonstrating that MPAs are having positive effects in mesophotic depths across the network as well as at previously reported shallower depths, and that image‐based platforms such as ROVs provide an important tool to support timely reporting on the effectiveness of MPA networks.